2021
DOI: 10.21776/tema.22.1.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, Dan Kebijakan Dividen Terhadap Nilai Perusahaan

Abstract: This study aims to determine the effect of institutional ownership, managerial ownership, and dividend policy on the firm value of basic industry and chemical companies listed in the Indonesia Stock Exchange between 2017 and 2019. This study utilises institutional ownership percentages to measure institutional ownership variable, managerial ownership percentages to measure managerial ownership variable, dividend payout ratio to measures dividend policy variable, and tobin's q ratio measures firm value. This ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
0
0
7
Order By: Relevance
“…The results of this research are in line with research by [29,37]. Based on previous research, the author found that managerial ownership has a positive effect on firm value, meaning that increasing the percentage of managerial ownership can increase firm value.…”
Section: The Influence Of Managerial Ownership On Firm Value In Lq45 ...supporting
confidence: 87%
“…The results of this research are in line with research by [29,37]. Based on previous research, the author found that managerial ownership has a positive effect on firm value, meaning that increasing the percentage of managerial ownership can increase firm value.…”
Section: The Influence Of Managerial Ownership On Firm Value In Lq45 ...supporting
confidence: 87%
“…Wald chi2(2) = . Kajian peneliti sesuai dengan yang ditemukan oleh (Sari & Wulandari, 2021) perihal kepemilikan institusional tidak mempengaruhi nilai perusahaan. (Schmidt & Fahlenbrach, 2017) menyebutkan bahwa kepemilikan institusional memainkan peran penting dalam penentu peningkatan institusi apabila dikelola secara pasif menyebabkan kepemilikan institusional tampaknya memiliki konsekuensi bagi tata kelola perusahaan.…”
Section: • Variabel Komite Audit Atas Nilai Perusahaanunclassified
“…Kepemilikan institusional dapat memoderasi hubungan antara CSR dengan nilai perusahaan sejalan dengan penelitian Fitriana (2019) dan Edison (2017) yang menyatakan bahwa kepemilikan institusional berpengaruh positif terhadap Corporate Social Responsibility, sehingga, semakin tinggi kepemilikan institusional, maka dapat mendorong peningkatan pengungkapan CSR. Namun penelitian ini bertolak belakang dengan penelitian yang dilakukan oleh Sari dan Wulandari (2021).…”
Section: Pengaruh Csr Terhadap Nilai Perusahaan Dengan Gcg Sebagai Mo...unclassified